TEACHING HORTATORY EXPOSITION WRITING USING GUIDED WH-QUESTIONS TO THE STUDENTS OF SMA PGRI 1 PONTIANAK GRADE XI - Cenderato Cenderato (STKIP Persada Khatulistiwa Sintang, 2020)
This research was conducted to answer the research question: “How effective is the use of Guided Wh-Questions to improve the students’ hortatory exposition writing?” The method of this research was a Pre-experimental Study by applying Pretest, the treatment and Posttest. The treatments were conducted in three time meetings with the purpose to know the effectiveness of the treatment using the Wh-question as a guide to write hortatory exposition.The population of this research was the students of class XI of SMA PGRI 1 Pontianak in academic year 2010 with 40 students of class XIA and Class XIB. But, 20 students of class XIB was considered as a sample of this research. The technique of data collecting was a written test that the students wrote hortatory exposition with the help of Wh-questions as a guide. The research findings showed the total score of pretest is 1286 with the mean score 64.30 and categorized “Average”. Furthermore, the result of posttest is 1493 with the mean score 74.63 and categorized “Good”.The result of computation on the t-test with 6,99 is higher than the t-table for the degree of freedom N-1 (20-1)=19 is 2.093. Effect Size of the treatment is 1. 53. It is categorized “Highly Effective” because the result of 1. 53 is higher than 0.8 that is the high level of effectiveness on Effect Size criteia proposed by Burn (ES > 0.8 = 1. 53 >0.8). In conclusion, the teaching hortatory exposition writing by using Guided Wh-questions is “highly effective”. Therefore, the null hypothesis that says “Teaching Hortatory Exposition Writing using Guided Wh-questions is not effective” is rejected. And the alternative hypothesis that says “Teaching Hortatory Exposition Writing using Guided Wh-questions is effective” is accepted. Keywords: Teaching, writing, Hortatory Exposition, Guided-WH questions